Death in the Line of Duty: Game Warden Mortality in the United States, 1886–2009 - Eliason, Stephen L. (American journal of criminal justice, 2011)
Game wardens are conservation law enforcement officers who enforce fishing and hunting laws. It has been suggested that the occupation of game warden is the most dangerous and deadly job in law enforcement. Little research, however, has been directed toward the study of game warden deaths. In an attempt to extend our understanding of the deadly nature of this occupation, this study examined the number and causes of line of duty deaths for state game wardens in the United States from 1886 to 2009. Findings suggest that gunfire was the most frequent cause of death of game wardens during this time period. Other factors responsible for large numbers of game warden fatalities included vehicle accidents, drowning, aircraft accidents, and heart attacks.